GROWTH RESPONSES OF OIL PALM (Elais gueneensis Jacg) SEEDS IN PRE-NURSERY ON DIFFERENT CLANTING MEDIA AND PROVISION OF POSTHOPIC FERTILIZER - Tommy Suranta Ginting; Razali Razali; Octanina Sari Sijabat; Yunida Berliana (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2022)
Introduction: This study aims to determine the effect of different planting media and phosphoric fertilizer application on the growth of oil palm seedlings (Elais guineensis, Jacg) in early nurseries. The short-term goal of this research is to know that phosphate fertilizer can affect the growth of oil palm seedlings. Materials and Methods: This research was carried out in Prestasi District, Langkat Regency, North Sumatra from January to April 2022. The method used in this study was a Factorial Randomized Block Design (RBD). It consists of two factors, namely: The first factor which consists of two treatments namely, M1: Top Soil, and Manure (1: 1), M2: Top Soil, and Sand (1: 1). The Second Factor consists of 3 factors namely, F = 0 CONTROL (without treatment), F1 = 3 grams/liter of water, F2 = 5 grams/liter of water. Variables observed were Plant Height, Stem Diameter, Number of Leaves, Leaf Area. Results The treatment of phosphate fertilizer application had no significant effect on plant height, stem diameter, number of leaves, and leaf area. The interaction of growing media and application of phosphate fertilizer had no significant effect on plant height, stem diameter, number of leaves, and leaf area. In general, the M1F1 interaction treatment (Top Soil: Manure and 3 grams of Phosphate) produced the highest values ​​for plant height, number of leaves, and leaf area.